If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(16x + 4) = 3(34 + x) Reorder the terms: 3(4 + 16x) = 3(34 + x) (4 * 3 + 16x * 3) = 3(34 + x) (12 + 48x) = 3(34 + x) 12 + 48x = (34 * 3 + x * 3) 12 + 48x = (102 + 3x) Solving 12 + 48x = 102 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 48x + -3x = 102 + 3x + -3x Combine like terms: 48x + -3x = 45x 12 + 45x = 102 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + 45x = 102 + 0 12 + 45x = 102 Add '-12' to each side of the equation. 12 + -12 + 45x = 102 + -12 Combine like terms: 12 + -12 = 0 0 + 45x = 102 + -12 45x = 102 + -12 Combine like terms: 102 + -12 = 90 45x = 90 Divide each side by '45'. x = 2 Simplifying x = 2
| 129=5(2a-1)+2a | | 4(3m-2)=16 | | -2(2s-4)-8=-2(8s+6)-3 | | 5x^2+2x+18=0 | | (33/2)-5 | | 3h+9=15 | | 2x+24(3-9)=91 | | x+4=6+3x | | -5s+16=-29 | | 3a+3-6a=15 | | 1x/2-3=5x/7+1 | | 3.5x+2.1y+9.9=0 | | -25=5(n+3)-5 | | 4x+5x-4+3x+2x+2=180 | | 3-3x=-21 | | 3x+4=-2x^2 | | 0.4y^3+0.3y^3-0.2y^3= | | 5-2(n+2)+6=16 | | f(x)=2x(x+3)-2x^2-6x+5 | | 2/3h-1/3h+11=8 | | 0.4y^3+0.3y^33-0.2y^3= | | x-9/4=7 | | 120+36x=12x | | Z^3=Z^2+30Z | | 28/9=x/1.8 | | 18=16t^2 | | f(x)=2x(7x+13)-9 | | -2r^2+5r+2=0 | | 7(d-2)=(5d+2) | | y=(5x-2)(5)-3x+17 | | b+9/12=-3 | | 2(m+5)-4(m+3)=6 |